Experimental study of fracture geometry characteristics on rock mass strength and crack propagation evolution law - Zhang, Huimei; Yuan, Chao; Chen, Shiguan; Yang, Gengshe; Xia, Haojun (European journal of environmental and civil engineering, 2022)
To explore the comprehensive effects of fracture geometric characteristics (length, penetration, quantity and dip angle) on rock mass strength, the uniaxial compression experiments were conducted on rock samples containing prefabricated fractures, the influence of fracture geometric characteristics on the deformation and failure of rock mass and the evolution law of crack propagation are systematically studied from macroscopic and microscopic perspectives. The results show that the conditions of uniaxial compression, the initial damage caused by prefabricated fracture further degrades the strength of rock samples. The rock sample mechanics process can be divided into the consolidation, secondary microcracks and crack extension and sample destruction of four stages, the peak strength, elastic modulus and peak strain of rock samples increase with the decrease of relative geometric characteristics. The failure form of intact rock sample was mainly tensile failure, the fracture (length and quantity) rock samples were subject to shear failure, the failure mode of rock sample with fracture penetration was mainly shear and supplemented by tension, the 0°, 30° and 90° fracture rock samples are X-shaped conjugate inclined plane shear failure, while the 45° and 60° fracture rock samples are shear failure.